La Compañía de Mejoras de Ensenada: análisis histórico del ascenso y fracaso de un empresa turística en Baja California (Tzintzun, Revista de Estudios Históricos, 2019)
At the beginning of the 1930s, the Playa Ensenada, hotel and casino, was inaugurated in Ensenada, Baja California, by the Ensenada Improvement Company. The investment that was made to build this hotel came from foreign capitalists who saw it feasible to develop a tourist complex more than 80 kilometers from the border that divides Mexico with the United States. It was idealized that, due to the border proximity, large numbers of American tourists would arrive to stay in a hotel whose main attraction was the calm and warm beach of the port of Ensenada, as well as its surroundings and to offer within the tourist complex, various recreational activities to its guests, as the practice of different games of chance in their facilities. But only eight years after it opened, the Playa Ensenada closed its doors definitively in 1938. The purpose of this paper is to analyze the factors that marked the early rise and failure of the Ensenada Improvement Company in Baja California, and thus promote interest in studying the development of the beginnings of the tourism sector in the state, especially those cases far from the border line.